HUBUNGAN KECANDUAN VIDEO GAME DENGAN KEBUTUHAN BERSOSIALISASI PADA REMAJA DI KELURAHAN TEGAL GEDE KECAMATAN SUMBERSARI - Rizki Eko Prasetyo; Yugi Hari Chandra (Jurnal Kesehatan dr. Soebandi, 2017)
Adolescence is a period of rapid growth and development both physically, psychologically and intellectually. It is often found that many adolescents who experience problems in the stages of development, especially on the problem of addiction to this game that affects the phase of social development. The purpose of this study was to determine the relationship between video game addiction and the need to socialize in adolescents. The research design used descriptive correlation with cross-sectional approach with a population of 67 respondents. The sampling method using Cluster Random Sampling obtained a sample of 60 respondents. This research was conducted by giving questionnaires to teenagers who were playing video games to find out the level of video game addiction and to know the level of social needs. The results of this study were analyzed using the Spearman Rho Correlation test, it was found that video game addiction in adolescents was mild addiction as much as 28.3%, moderate addiction as much as 28.3%, and severe addiction as much as 43.3%. While the need for socializing results obtained low needs of 20.0%, medium needs of 55.0%, and high needs of 25.0%. From the results of the analysis of the two variables obtained p value = 0.002 (<α = 0.05) then Ha is accepted which shows there is a relationship between video game addiction and the need to socialize in adolescents. It is recommended for adolescents to be wiser in following the times